EQUIPMENT NOWADAYS - Mirzayev Islombek Umarali o’gli (European Science Publishing, 2023)
Today, the development of technology and the types of new technologies are being developed a lot. This technology includes Digital Cameras, Laptops, Pocket Computers, and many other techniques, these technologies are in demand. Digital cameras NIKON The design of this camera leaves a good effect on a person. It can be collected in a small and thin state (108x73x69 ml) as well as in a frog pocket
Keywords: You need to select an SQ screen. And there will always be a boulecy, and you will not sit digging up every dafar menu again. I didn't like optical video because it's too small and the eye needs to be made too close to it. Therefore, it is easy to work with a enabled SQ display and is slave.